Physiological and subjective responses associated to physical and mental load in a simulated task - Hernandez Arellano, Juan Luis (2018)
Objective: To develop a quasi-experimental study to know the changes in physiological responses and perceived efforts of a group of fifteen healthy students that performed a simulated task related with the operation of a cnc lathe in a lab environment. Materials and Methods: The participants were asked to randomly complete a total of eight sessions including single and combined test of physical and mental load. Low/High Physical Load and Low/ High Mental Load were established as independent variables. Heart rate, physical performance, mental performance, and effort perception were established as dependent variables. Conclusions: High load levels have a significant effect on the heart rate increasing, but not in the perception of effort. High levels of mental load have a significant effect on physical and mental performance.